Innovation, adaptation and technology as habitus: the origins of alluvial gold mining methods in Australia. (April 2015) - Lawrence, Susan; Davies, Peter
Abstract: The introduction of Cornish mining methods during the Australian gold rush provides a case study for examining the role of technological innovation in the context of migration. New physical and social environments encountered as a result of migration force migrants to adapt familiar technologies to their new circumstances. Cornish migrants to Australia were able to apply their knowledge of traditional methods for working alluvial tin deposits to the exploitation of alluvial gold. These methods were heavily dependent on reliable sources of water, and in order to ensure success, the miners developed innovative technical and legal systems for managing water supplies.